ASSESSING THE EFFECTIVENESS AND EXPOSITORY METHOD ON THE ACHIEVEMENT OF BASIC SCIENCE STUDENTS IN DIFFERENT LEVELS OF SCIENTIFIC LITERACY (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This  study  investigated  the  effect  of  schools  supervision  on  the  academic performance of Basic science students in Ahoada East Local Government Area of Rivers State, Nigeria. Six research questions and six hypotheses were raised to guide this study. A descriptive survey design was adoptedfor the study with a study population  of  two  hundred  (200) junior  secondary  school  students,  and  one hundred and seventy five (175) junior secondary schools was used for the study through  a  multi-stage  sampling  technique  which  was  adopted to  select  three hundred and seventy – five (375)  participants. Structured questionnaires were used for data collection and all were analyzed, using simple percentage and chi- square statistical tool to test the hypotheses at 0.05 level of significance. The result of the study revealed the level of effect school supervision has on the academic performance of secondary school students on Basic science which was  76.9% indicating that more than half of the total respondents as opposed to less than 40% of the respondents that indicated 24.1% and based on that, it was concluded that the rate of school supervision is directly proportional to the academic performance of secondary school students  on Basic science as a hallmark for educational improvement. It was recommended that government should increase  effort on finding school supervision as to improve the quality of education which are of great significance toward students’ academic performance.